Colony composition, brood production and caste dimorphism in two species of the doryline genus Lioponera in the Oriental tropics (Formicidae: Dorylinae) - Ito, Fuminori; Jaitrong, Jaitrong; Hashim, Rosli; Mizuno, Riou (Penerbit Universiti Malaysia Sabah, 2018)
Recent phylogenetic research indicates that the true army ants (e.g. Aenictus, Dorylus, Eciton, Neivamyrmex) belong to the subfamily Dorylinae, together with several non-army ant genera such as Cerapachys, Yunodorylus, Lioponera and Ooceraea. Thus, comparative studies among doryline genera are very important for understanding the biological characteristics of true army ants. We investigated colony composition of two species of the Lioponera suscitata group in the field and in the laboratory in Indonesia, Malaysia, and Thailand. In both species, queens were alates, and queen-worker dimorphism in body size was weak. Two queenright colonies of L. suscitata were monogynous, with 14 and 40 workers each, and one orphan colony had 30 workers. The colony of Lioponera sp. collected in Thailand had two queens and 12 workers. Colonies of both species included all developmental stages of brood. In the laboratory, the queen of Lioponera suscitata continuously laid eggs, and the captive colony always had all developmental stages of brood. This shows that reproduction in these two species is non-phasic.